Narratives of Islamic Origins The Beginnings of Islamic Historical Writing. - Donner, Fred M. (SLAEI - Studies in Late Antiquity and Early Islam Ser., 2020)
How and why did Muslims first come to write their own history? The author argues in this work that the Islamic historical tradition arose not out of idle curiosity, or through imitation of antique models, but as a response to a variety of challenges facing the Islamic community during its first several centuries. In the first part, the author presents an overview of four approaches that have characterized scholarship on the literary sources, including the source-critical and the skeptical approaches, then it discusses historiographical problems raised by the Qur'an and Hadith. In the second pa.